Incidence and Prevalence Trends of Pediatric Inflammatory Bowel Disease in the Daegu-Kyungpook Province From 2017 to 2020 - Choe, Jae Young; Choi, Sujin; Song, Ki Hwan; Jang, Hyo-Jeong; Choi, Kwang-Hae; Yi, Dae Yong; Hong, Suk Jin; Hwang, Jun Hyun; Cho, Seung-Man; Kim, Young Jin; Choe, Byung-Ho; Kang, Ben (Frontiers in Pediatrics, 2022)
Background and Aim: There is paucity of data regarding the epidemiology of pediatric IBD in Asia compared to that of Western countries. We aimed to investigate the incidence and prevalence trends of pediatric inflammatory bowel disease (IBD) in the Daegu-Kyungpook province of South Korea from 2017 to 2020. Methods: This study was a multicenter, retrospective study conducted in eight IBD referral centers located in the Daegu-Kyungpook province. Children and adolescents of ≤18 years who were initially diagnosed with IBD between 2017 to 2020 were included. The annual number of children and adolescents newly diagnosed with IBD and the annual resident population of children and adolescents ≤ 18 years of age in the Daegu-Kyungpook province were investigated to calculate the annual incidence and prevalence in the region. Results: A total 304 children and adolescents that had been diagnosed with IBD were included in this study. Among these patients, 71.4% had been diagnosed with Crohn’s disease (CD), and 28.6% with ulcerative colitis (UC). The population based annual incidences of IBD from 2017 to 2020 were each 7.24, 6.82, 10.27, and 13.33 per 100,000, respectively (P for trend<0.001), 4.48, 5.26, 7.39, and 9.8 per 100,000, respectively for CD (P for trend<0.001), and 2.76, 1.56, 2.88, and 3.53 per 100,000, respectively for UC (P for trend=0.174). Conclusion: Pediatric IBD, especially CD has significantly increased recently in the Daegu-Kyungpook province. Epidemiology studies from other regions of Asia are required to better elucidate this trend of increase in Asia.